2017
DOI: 10.1037/ccp0000144
|View full text |Cite
|
Sign up to set email alerts
|

Improving homework performance among children with ADHD: A randomized clinical trial.

Abstract: Objective Evidence indicates that children with Attention Deficit Hyperactivity Disorder (ADHD) experience acute and prolonged academic impairment and underachievement including marked difficulty with completing homework. This study is the first to examine the effects of behavioral, psychostimulant, and combined treatments on homework problems, which have been shown to predict academic performance longitudinally. Method Children with ADHD (ages 5-12, N = 75, 71% male, 83% Hispanic/Latino) and their families … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 56 publications
1
23
0
6
Order By: Relevance
“…If some causes are quite rare, they should be considered after more common causes have been explored. As previously stated, ADHD affects approximately 9% of school-age children (Danielson et al, 2018), making it the most common mental health disorder among children (Merrill et al, 2017). The gifted field, in general, has been wary of the misdiagnosis of ADHD (Baum, 1998; Baum & Olenchak, 2002; Baum et al, 1998; Hua et al, 2014; Webb et al, 2005), yet considering the possibility of ADHD for underachieving gifted students may be particularly valuable.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…If some causes are quite rare, they should be considered after more common causes have been explored. As previously stated, ADHD affects approximately 9% of school-age children (Danielson et al, 2018), making it the most common mental health disorder among children (Merrill et al, 2017). The gifted field, in general, has been wary of the misdiagnosis of ADHD (Baum, 1998; Baum & Olenchak, 2002; Baum et al, 1998; Hua et al, 2014; Webb et al, 2005), yet considering the possibility of ADHD for underachieving gifted students may be particularly valuable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students with ADHD often struggle to achieve academically (Merrill et al, 2017). Early research in this area suggested that the presence of low achievement for students with ADHD was nearly 20% (Frick & Lahey, 1991).…”
Section: Defining Attention-deficit/hyperactivity Disordermentioning
confidence: 99%
“…However, these therapies often do not generalize well to other aspects of the child’s life beyond the specific behaviors trained. A recent randomized clinical trial found that, for elementary school children who attended a rigorous six-week summer behavior training program, those whose parents participated in twelve hours of behavioral training performed substantially better on their homework than children in the program who took ADHD medication (Merrill et al 2017). Although these results are encouraging, it remains to be seen whether such a program would be feasible outside of an intensive summer school setting.…”
Section: Objectivementioning
confidence: 99%
“…Se ha comprobado mediante ensayo clínicos que los cumplidores del programa Challenging Horizons Program, vinculado a la TC, mostraron beneficios importantes en la organización, comportamientos disruptivos, desempeño de la tarea y calificaciones, respecto a los controles, con resultados que perduraron 6 meses después del término del tratamiento (Schultz, Evans, Langberg & Schoemann, 2017). En la misma línea el TC (entrenamiento para padres enfocado en la tarea y un boletín de calificaciones diario) centrado en las tareas escolares presenta beneficios claros para la terminación y exactitud de la tarea de los niños, mientras que la medicación estimulante de acción prolongada dio lugar a efectos limitados y no significativos (Merrill et al, 2017). También se ha demostrado mediante un ensayo clínico que cuando el programa de tratamiento Child Life and Attention Skills involucra conjuntamente a padres, profesores y niños el resultado es mejor que realizado solo con los padres o con el tratamiento habitual.…”
Section: Terapia De Conducta (Tc)unclassified